EDUKASI PENCEGAHAN, PENANGANAN COVID-19, DAN PEMAHAMAN PEMANFAATAN VAKSINASI BAGI WARGA DESA LINGGA SIRNA KECAMATAN SARIWANGI KABUPATEN TASIKMALAYA - Gugum Gumilar; Depi Ardian Nugraha; Agi Ahmad Ginanjar (Lembaga Pengembangan Kinerja Dosen, 2022)
The lack of public awareness in implementing Health protocols in the prevention and handling of Covid-19 is the reason for providing education or knowledge of citizens on the importance of maintaining health protocols. The objectives of this community service program are 1) to increase public knowledge and provide correct information on how to prevent and handle Covid-19, 2) to help realize government programs so that they can run the Clean and Healthy Lifestyle (PHBS) and Healthy Living Community Movement (PHBS) program. GERMAS) which is programmed by the government such as washing hands in running water, using hand sanitizer, using mouth masks, maintaining distance, 3) assisting the government in disseminating correct information about how to prevent and handle COVID-19 through mass media, both print media such as brochures. / leaflets and electronically through social media, 4) increase the sense of security and comfort for the community to carry out activities outside the home such as worshiping in public places and other activities, because disinfectants have been sprayed regularly in certain places, 5) assisting the government in implement a vaccination program mass by providing correct information and knowledge about the vaccination program as a preventive effort to prevent and handle covid-19 and 6) the realization of people who are aware of the importance of maintaining health. The method of activities carried out is using the Participatory Rural Appraisal (PRA) approach, Observation, Focus group discussion (FGD) approach, counseling, mentoring/monitoring, providing follow-up and program evaluation. The results of this activity showed a very positive response from the residents of the Linggasirna Community, Sariwangi District, Tasikmalaya Regency with this activity, we even received a report from the village head that more than 60% of residents who had vaccinated so far had only 15% of the total population. inhabitant. The outputs of this activity are: 1) publication in local print mass media, and 2) producing scientific publication articles published in accredited National Journals with ISSN.